(untitled) (Journal Of Educational and Psychological Researches, 2024)
The research aims to identify the social interaction of kindergarten children, the significance differences in social interaction between boys and girls, the significance differences of kindergarten type in social interaction (governmental, private), and the significance differences of the mother’s profession in social interaction (housewife, working). To achieve these objectives, the researcher adopted Adel Abdullah Muhammad’s scale for children’s social interactions, the scale was used for a random sample of mothers whose children were enrolled in governmental and private kindergartens across the six districts of Baghdad. The sample size consisted of 350 mothers. The researcher confirmed the reliability and validity of the scale by presenting it to a group of experts and specialists in kindergarten, psychological and educational sciences, measurement, and evaluation. Psychometric characteristics of the scale were derived using indicators of validity and reliability, and the statistical program SPSS was employed to perform statistical analyses such as analysis of variance, t-test, standard deviation, mean, and Cronbach’s alpha equation. The results revealed that the research sample has a high level of social interaction. There were significant differences in social interaction between boys and girls in favor of boys. There were significant differences in social interaction based on the type of kindergarten, where governmental kindergartens showed more favorable outcomes. There were significant differences in social interaction based on the mother’s profession; housewives had more favorable outcomes